Morphology and phylogeny of Pararaabena dentata Wolska, 1968 and further insights into the molecular evolution of trichostome ciliates (Ciliophora, Litostomatea) - Gürelli, Gözde; Kesbiç, Fevziye Işıl (Elsevier BV, 2024)
The morphology and phylogenetic position of a trichostome ciliate, Pararaabena dentata, isolated from the intestine of an Asian elephant (Elaphas maximus) in Gaziantep Zoo, Turkey, were studied using pyridinated silver carbonate impregnation, scanning electron microscopy, and the 18S rRNA gene. Pararaabena dentata clustered together with Raabena bella and both taxa were phylogenetically not related to members of the family Blepharocorythidae, as expected in the past. Phylogenetic trees indicated that amphibian intestinal ciliates represented by Balantidium grimi, B. duodeni, and B. entozoon are basal to all other trichostome ciliates, causing the family Balantidiidae to be polyphyletic. The molecular evolution of the subclass Trichostomatia is thoroughly discussed.
Keywords: Evolution, Molecular; Species Specificity; RNA, Ribosomal, 18S; Microscopy, Electron, Scanning; Animals; Ciliophora; Phylogeny